Perbandingan OCB Sebelum dan Sesudah Program E-Kinerja Di Puskesmas Puncu - Dirgandaru Panggayuhan (Jurnal Simki Economic, 2019)
This research was motivated by the existence of the E-Kinerja program which was implemented in 2016 and encouraged changes to the organizational culture at the Puncu Health Center. Especially for employees with civil servant status (PNS) who will receive the greatest impact from changes in the work environment and organizational culture. This causes differences in behavior, especially organizational citizenship behavior (OCB), which is an extra role behavior and tries to work beyond the standard assessed from before and after the E-Kinerja program is run. This study aims to compare the level of OCB before and after the implementation of the E-Kinerja program at PUSKESMAS PUNCU. This research approach is quantitative with a comparative research type. The sample of this study is a saturated sample, with a total of 30 PUSKESMAS PUNCU employees. This study uses primary and secondary data, primary data comes from direct respondents' answers. Secondary data comes from literacy and the official website of UPTD PUSKESMAS PUNCU. The analytical technique used in this research is descriptive statistics, normality test and paired sample t-test and Wilcoxon non-parametric test. The results of this study indicate that there are differences in the OCB level of employees after the implementation of the E-Kinerja program with the results of the paired sample t-test difference test per indicator significance value <0.05 from each dimension on the Morison scale. The significance value for the altruism dimension is 0.000, for the significance value for the sportsmanship dimension is 0.000, for the significance value for the civic virtue dimension is 0.000, for the courtesy dimension significance value is 0.000, while the conscientiousness dimension significance value for the non-parametric Wilcoxon test is 0.000.